PROJECTED SCENARIO OF BIOFORTIFIED RICE NEEDS IN FIVE PRIORITY PROVINCES TO REDUCE STUNTING - Amalina, Dian; Yazid, M; Ritonga, Utan Sahiro (Departemen Sosial Ekonomi Faperta Unpad dan Perhepi Komisariat Bandung, 2025)
Abstract The problem of malnutrition and hidden hunger is still a challenge in Indonesia, with an uneven prevalence of stunting between regions. Nutrition interventions require a targeted approach. This study aims to analyze the market potential and project the demand for biofortified rice specifically in the five priority provinces with the highest stunting prevalence: Aceh, NTB, NTT, West Sulawesi, and Southwest Papua. This study uses a descriptive quantitative method with projection and scenario analysis. Secondary data from BPS, SUSENAS, and SSGI were analyzed to map the potential for market uptake using pessimistic (5%), moderate (15%), and optimistic (30%) adoption scenarios. The results of the analysis show a very significant economic potential. In the moderate adoption scenario (15%), the total estimated market value of biofortified rice in the five provinces collectively has the potential to reach Rp 16.987 trillion per year. Volume demand in the same scenario is projected to grow consistently, reaching 241,970 tons by 2030. These findings confirm that biofortified rice has a strong economic justification as an investment opportunity and nutritional intervention. This research provides quantitative targets for stakeholders to design effective production and distribution strategies in these priority areas.Keywords: Food Investment, Rice Needs, Biofortified Foods, Nutritional Problems, Food Demand.